2013
DOI: 10.1523/jneurosci.5632-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala Lesions Reduce Cataplexy in Orexin Knock-Out Mice

Abstract: Narcolepsy is characterized by excessive sleepiness and cataplexy, sudden episodes of muscle weakness during waking that are thought to be an intrusion of REM sleep muscle atonia into wakefulness. One of the most striking aspects of cataplexy is that it is often triggered by strong, generally positive emotions, but little is known about the neural pathways through which positive emotions trigger muscle atonia. We hypothesized that the amygdala is functionally important for cataplexy because the amygdala has a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
84
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 69 publications
1
84
0
2
Order By: Relevance
“…This hypothesis explains dysregulated sleep/wake cycling associated with orexin neuron loss in NC, but does not explain cataplexy symptoms. How cataplexy relates to motivational or arousal functions of the orexin system is controversial, but a link to emotional arousal is clear 7,11,19,23,2729 (Box 1). …”
Section: The Many Faces Of Orexin/hypocretin Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis explains dysregulated sleep/wake cycling associated with orexin neuron loss in NC, but does not explain cataplexy symptoms. How cataplexy relates to motivational or arousal functions of the orexin system is controversial, but a link to emotional arousal is clear 7,11,19,23,2729 (Box 1). …”
Section: The Many Faces Of Orexin/hypocretin Functionmentioning
confidence: 99%
“…Cataplexy involves brief episodes of muscle atonia (paralysis) with maintained consciousness, often triggered by strong positive emotional stimuli in humans and animals 3,6,8,11,28,29 .…”
mentioning
confidence: 99%
“…3 Inhibitory connections between the amygdala and "REM-off" area trigger cataplexy in response to positive stimuli in hypocretin knock-out (KO) mice with a decrease following bilateral amygdala lesions. 4 Human studies have shown that narcolepsy patients have altered responses to positive emotional stimuli and reward. 5,6 These studies suggest the amygdala and hypocretin neurons are active in response to positive emotional states.…”
Section: Discussionmentioning
confidence: 99%
“…4 Human studies have shown that narcolepsy patients have altered responses to positive emotional stimuli and reward. 5,6 These studies suggest the amygdala and hypocretin neurons are active in response to positive emotional states.…”
mentioning
confidence: 99%
“…Thus, a vital flexibility of arousal is lost without orexin/hypocretin. In terms of robustness, it is well known that without orexin/hypocretin arousal can dip to inappropriately low levels (unconsciousness) upon disturbances such as laughter in humans or sight of delicious food in animals [2,117,118]. Without orexin/hypocretin, there is no appropriate tracking/adjustment of arousal state to internal and external state.…”
Section: Mapping Orexin/hypocretin Biology Onto Control Operationsmentioning
confidence: 99%